She stoops to conquer : a comedy in three acts / by Oliver Goldsmith. - Goldsmith, Oliver, 1730?-1774. (Tufts University. Tisch Library., 2015)
1 online resource (64 pages); "First performed at Covent Garden, March 15th, 1773"--Title page verso.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.